Identification and Molecular Characterization of Thermo Tolerant Fecal Coliforms and Bacterial Pathogens “E.coli, Salmonella spp and Shigella spp” in Ein-Elbalad Spring in Battir - Danho, Joseph (Palestine Polytehnic University & Bethlehem University)
Battir is a Palestinian village located 6.5km north-west Bethlehem city with a population of approximately 5000 people. Ein El-Balad spring is a vital water source in Battir since water supply for the village is not available all the time especially in summer season. Recent reports indicated a serious contamination in the spring water. Among many sources of contamination, waste water intrusion from cesspits is the major source of contamination for the spring. Molecular techniques provide a powerful robust analysis in detection of bacterial cells in water even if they exist in small quantities. In this thesis the presence of thermo-tolerant fecal coliform bacteria in the spring have been identified using membrane filter culture technique and some coliform isolates were characterized by polymerase chain reaction (PCR) targeting the 16S rDNA gene followed by Sanger sequencing. In addition the possible presence of bacterial pathogens E.coli, Salmonella spp and Shigella spp has been detected by PCR using species specific primers followed by MISeq next generation sequencing. Results showed a high number of thermo-tolerant fecal coliform bacteria and the presence of coliform isolates that are of a pathogenic nature, moreover PCR detection using species specific primers has shown that the spring water does not contain any Salmonella or Shigella species but contain E.coli. Next Generation Sequencing analysis targeting E.coli bacteria indicated the presence of waterborne pathogenic strains of E.coli بتير هي قرية فلسطينية تقع 5,6كم شمال غرب بيت لحم ويبلغ عدد سكانها تقريبا 5000 نسمة نبع عين البلد في بتير هو مصدر هام للمياه في القرية حيث ان إمدادات المياه للقرية لا تكفى احتياجاتها في كل وقت وخاصة في فصل الصيف. تشير التقارير الأخيرة إلى تلوث خطير في مياه النبع، ومن بين العديد من مصادر التلوث تشكل تسرب المياه العادمة من الحفر الامتصاصية المصدر الرئيسي للتلوث في هذا النبع. توفر التقنيات الجزيئية التحليل الدقيق والقوي في الكشف عن مسببات الأمراض في المياه حتى تلك الموجودة بكميات صغيرة جدا. في هذا الاطروحة تم الكشف عن وجود بكتيريا القولونيات البرازية المقاومة للحرارة في مياه النبع باستخدام تقنية الفلترة بالغشاء وتم تمييز بعض العزلات باستخدام تفاعل البلمرة المتسلسل الذي يستهدف جين (16S rDNA) متبوعا بتقنية سانجر لكشف التسلسل الجيني. بالإضافة الى ذلك تم الكشف عن امانية وجود البكتيريا المسببة للمرض الإشريكية قولونية، السلمونيلا والشيغيلا باستخدام تفاعل البلمرة المتسلسل الذي يستهدف النوع البكتيري بشكل خاص متبوعا بتقنية المايسك للتسلسل الجيني من الجيل الثاني. أظهرت النتائج وجود عدد كبير من البكتيريا القولونية في مياه النبع وأظهر التصنيف الجزيئي لبعض العزلات من بكتيريا القولونيات البرازية ان معظم هذه العزلات ذات طابع مسبب للمرض. النتائج الخاصة بالكشف عن البكتيريا المسببة للامراض إشراكية قولونية. السلمونيلا والشيغيلا اظهرت خلو المياه من السلمونيلا والشيغيلا وتاكيد وجود الإشراكية قولونية. كشفت تقنية المايسك لتسلسل الجيني من الجيل الثاني التي استهدفت بكتيريا الإشراكية قولونية عن وجود يكتيريا الإشراكية قولونية ذات طابع مسبب للمرض من خلال المياه.
CD 29367_ NO. of pages 62
Keywords: Science in Bitechnology